FULFILLMENT OF PRISIONERS RIGHTS IN CLASS II-A WOMEN PRISONS IN SEMARANG - Luvi Amalia; Eta Yuni Lestari (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
AbstractWomen inmates have rights that must be protected in accordance with the mandate of the constitution, moreover women have a different nature from men. But looking at the existing reality, there are still correctional institutions that experience overcapacity so that the fulfillment of rights has not been carried out optimally. One of them is the Semarang Class II-A Women's Correctional Institution with a total population of 249 people as of September 2020, even though the capacity is 174 people. The purpose of this study is to describe the fulfillment of the rights of prisoners and efforts to fulfill the rights of prisoners in the Class II-A Women's Correctional Institution Semarang. This study uses a qualitative approach with data collection methods through interviews, observation, and documentation. The data analysis technique uses an interactive model with the stages of data collection, data reduction, data presentation and conclusion drawing. The results showed that the fulfillment of prisoners' rights went well such as the right to worship, spiritual and physical care, education, health and food, submitting complaints, getting reading materials, premiums, receiving visits, remission, assimilation, political rights. While the rights that are still lacking are: access to wartelsus and video telephones, provision of equipment and food portions for prisoners. Efforts to fulfill the rights of prisoners at the Class II-A Women's Correctional Institution in Semarang, namely, providing guidance according to regulations, managing finances well, maintaining and caring for facilities, evaluating work, arranging schedules appropriately, appointing prisoners as tamping, cooperation with other parties, increasing service innovation.